Seismic exploration for volcanogenic massive sulphides-The DeGrussa copper-gold Mine, Western Australia - Kinkela, J.; Ziramov, Sasha; Dzunic, Aleksandar; Urosevic, Milovan; Hilliard, P. (EAGE Publishing BV, 2014)
Traditional geophysical prospecting techniques used for mineral exploration rarely provide the resolution required to accurately target orebodies at depth. Based on this, the seismic reflection method was trialled over a known VMS orebody at the DeGrussa copper-gold mine, Western Australia, in the hope of providing a viable exploration tool for deeper depths of investigation. However, a structurally complex geologic setting and a thick, highly variable regolith caused significant challenges in the processing of the seismic data. This paper addresses these challenges and looks at strategies used to overcome them eventually leading to the direct imaging of the orebody.